2021
DOI: 10.3390/polym13071012
|View full text |Cite
|
Sign up to set email alerts
|

Use of Artificial Neural Networks to Optimize Stacking Sequence in UHMWPE Protections

Abstract: The aim of the present work is to provide a methodology to evaluate the influence of stacking sequence on the ballistic performance of ultra-high molecular weight polyethylene (UHMWPE) protections. The proposed methodology is based on the combination of experimental tests, numerical modelling, and Artificial Neural Networks (ANN). High-velocity impact experimental tests were conducted to validate the numerical model. The validated Finite Element Method (FEM) model was used to provide data to train and to valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(46 reference statements)
0
2
0
1
Order By: Relevance
“…The primary principle behind these networks is based on how the biological brain system processes data and information to learn and produce knowledge. The creation of new methods for information processing systems is a major component of this concept [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The primary principle behind these networks is based on how the biological brain system processes data and information to learn and produce knowledge. The creation of new methods for information processing systems is a major component of this concept [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…La velocidad de impacto para esta prueba es de 420 m/s. El chaleco antibalas está compuesto por nueve capas independientes modeladas con elementos 3D con propiedades del material ortotrópicas, definidas con una subrutina de usuario [16].…”
Section: Impacto En Hueso-gelatina Simplificadounclassified
“…[5][6][7] The impact of stacking sequences on the lowvelocity impact behavior of UHMWPE composites was investigated in a study by Wu et al [8] The AE45°specimen exhibited the highest contact response, the smallest center-to-center displacement, and the highest post-impact compressive strength (C.A.I.). An artificial neural network (ANN) was developed by Peinado [9] to optimize the stacking sequence of UHMWPE laminates. The study's results demonstrated that combining the three UHMWPE materials improved ballistic performance compared to using only the highest-grade material.…”
mentioning
confidence: 99%